(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
This article examines the concept of competence, as well as the structural components of communicative competence such as motivational, axiological, informational and contentbased, and operational-activity-based. It provides a detailed analysis of the opinions of scientists on the development of communicative competence in future teachers